The structure optimisation of hydraulic mechanical screw pump. (2019) - Ma, Zhenfu
In the current stage of oilfield development, the screw pump is an advanced mechanical oil recovery process. In the oil and liquid lifting process, the screw pump with pumping force, high pressure, and strong pumping role requires good stable characteristics. This paper takes Shengli Oilfield water flooding development as the engineering background, aiming at the problem that the flow ratio of screw motor and screw pump affects the efficiency. The changing rules of influencing factors, such as luffing coefficient, eccentric coefficient, overflow area and relative sliding velocity, are analysed. With the amplitude coefficient and eccentric coefficient as decision variables, the paper optimises the equatorial short hypochromic curve to, get the best ratio of each head of the parameters and end line type.